FUNGSI PELAKU DALAM CERITA RAKYAT TOMANURUN (KAJIAN MORFOLOGI VLADIMIR PROPP): THE FUNCTION OF ACTORS IN TOMANURUN FOLKLORE (VLADIMIR PROPP MORPHOLOGICAL STUDY) - Midian; Nensilianti; Syam Saguni, Suarni (Journal of Applied Linguistics and Literature, 2023)
This study aims to analyze the function of actors in Toraja Tomanurun folklore which is studied using Vladimir Propp's morphological theory. This type of research is qualitative research. The research design used is descriptive research. The research data is in the form of text contained in the Toraja Tomanurun folklore and the data source is the Toraja Tomanurun folklore, 55 pages, published in 2016. The data collection technique is a documentation technique. The results showed that there were 15 functions of the actor which included absence, prohibition, violation, conveying information, crime or lack, departure, first donor function, hero reaction, moving place, tagging, needs fulfilled, coming unknown, difficult task, solving and being recognized.